Microbial Status of Sun-Dried Fish (Wazef) Sold in Different Yemeni Markets - Shamsan, Ebtisam F; Al-Jobory, Hala J (PSM Biological Research, 2018)
Heading from the fact that Yemenis consumers bother more about quantity and less about quality as a result they buy the product without considering health implications, this study concerned with the microbial analysis of 25 samples of sun-dried fish (Wazef) collected randomly from three different Yemeni cities. The bacterial count ranged from 1.4×102 – 4.6×105 cfu/g, while fungal counts ranged from 1.1×101 – 7.2×103 cfu/g. Ten bacterial species were obtained that belonged to 8 genera; Klebsiella, Bacillus, Staphylococcus, Pseudomonas, Serratia, E. coli, Streotococcus, and Lactobacillus, from which Klebsiella was the most dominant with a frequency of 28% of the samples. The mycological analysis revealed the presence of 26 fungal species in samples which belonged to 11 genera; Alternaria, Aspergillus, Eurotium, Hemicola, Mucor, Penicillium, Rhizopus, Scopulariopsis, Trichophyton, Trichoderma and yeasts, from which M. racemosus and Rhizopus stolonifer were the most dominant with an equivalent presence (84%) of samples. Findings of this study will increase the knowledge base towards adoption of improved handling and drying methods hence minimize microbial growth and possible contamination in the dried fish sector.